Adherence of mentally stable schizophrenic patients to antipsychotic medication at a mental health institution in the Limpopo Province - Molaba, Ramatsobane Granny (University of Limpopo (Turfloop Campus), 2013)
Adherence to antipsychotic medication is very important to patients with schizophrenia. Therefore, if patients with schizophrenia are non-adherent to treatment, they are at risk of relapse and being re-admitted at a mental health care institution in the Limpopo Province. Despite the proven benefits of antipsychotic medications, half of the patients with schizophrenia do not take their prescribed drugs. The researcher has observed the following occurrences during practice: • Lack of adherence to antipsychotic medications of schizophrenic patients results in symptoms not being relieved, poor drug effectiveness and patients developed other serious or costly consequences, such as being violent and damaging property; • High rate of relapse; and • High rate of re-admissions. This research questions has guided the study: • What are the factors affecting adherence of mentally stable schizophrenic patients to antipsychotic medications at a mental health institution in the Limpopo Province? • Do mentally stable schizophrenic patients adhere to prescribed treatment? • Are there any guidelines used to promote adherence to antipsychotic treatment? The aim of the study has been to determine the level of adherence of mentally stable schizophrenic patients to antipsychotic medication at a mental healthcare institution in the Limpopo Province. The objectives of the study have been to describe adherence of mentally stable schizophrenic patients to antipsychotic medication at a mental health institution in the Limpopo Province. It implies that participants have been given the opportunity to describe their experience while on medication. vi Their responses have led to the development of guidelines to promote adherence of mentally stable schizophrenic patients to antipsychotic medication. The study site has been the Thabamoopo Mental Healthcare Institution in the Capricorn District of the Limpopo Province. A descriptive, exploratory and contextual qualitative research design has been used in this study. The population has consisted of all mentally stable schizophrenic patients and all the carers of such patients. Non-probability purposive sampling has been used to select participants in this study. The researcher has used a semi- structured interview with two schedule guides for the patient and carers/relatives, which have specified the issues and questions covered. It has assisted the researcher with gathering information about the problem studied (De Vos et al. 2005).A total of twenty (n = 20) participants, consisting of fourteen (n = 14) mentally stable schizophrenic patients and six (n = 6) carers/relatives has been included voluntarily in the semi-structured interview sessions. The steps of data analysis as described by Tesch (1990) in Cresswell (1994) have been followed in this study. The findings of this study reveal a central storyline which indicates that participants share the same point of view in connection with aspects of adherence to antipsychotic treatment and also knowledge about the causes of mental illness and its prognosis. The following four themes and their sub-themes have emerged during data analysis: Theme 1: Participants share the same point of view related to aspects of adherence to antipsychotic treatment; Theme 2: Knowledge related to mental illness; Theme 3: Health seeking behaviours of mentally ill patients; and Theme 4: Experiences of relatives caring for mentally stable patients on treatment. Guidelines and recommendations based on the findings of this study are described in Chapter 4. The criteria for establishing the trustworthiness of qualitative data maintained in this study have been: Credibility, dependability, confirmability and transferability. The following ethical principles have been adhered to: The principle of beneficence, justice, the principle of human respect and dignity, permission to conduct the study, informed consent and confidentiality, privacy and anonymity.
Thesis (M.Cur) --University of Limpopo, 2013
Keywords: Antipsychotic medication; Schizophrenic patients; Schizophrenia; 615.5; Mental health; Patients compliance